Interactions between the introduced European honey bee and native bees in urban areas varies by year, habitat type and native bee guild - Prendergast, Kit; Dixon, Kingsley; Bateman, Bill (OXFORD UNIV PRESS, 2021)
European honey bees have been introduced across the globe and may compete with native bees for floral resources. Compounding effects of urbanization and introduced species on native bees are, however, unclear. Here, we investigated how honey bee abundance and foraging patterns related to those of native bee abundance and diversity in residential gardens and native vegetation remnants for 2 years in urbanized areas of the Southwest Australian biodiversity hotspot and assessed how niche overlap influenced these relationships. Honey bees did not overtly suppress native bee abundance; however, complex relationships emerged when analysing these relationships according to body size, time of day and floral resource levels. Native bee richness was positively correlated with overall honeybee abundance in the first year, but negatively correlated in the second year, and varied with body size. Native bees that had higher resource overlap with honey bees were negatively associated with honey bee abundance, and resource overlap between honey bees and native bees was higher in residential gardens. Relationships with honey bees varied between native bee taxa, reflecting adaptations to different flora, plus specialization. Thus, competition with introduced bees varies by species and location, mediated by dietary breadth and overlap and by other life-history traits of individual bee species.